2015
DOI: 10.1186/s12014-015-9099-0
|View full text |Cite
|
Sign up to set email alerts
|

Label-free mass spectrometric analysis reveals complex changes in the brain proteome from the mdx-4cv mouse model of Duchenne muscular dystrophy

Abstract: BackgroundX-linked muscular dystrophy is a primary disease of the neuromuscular system. Primary abnormalities in the Dmd gene result in the absence of the full-length isoform of the membrane cytoskeletal protein dystrophin. Besides progressive skeletal muscle wasting and cardio-respiratory complications, developmental cognitive deficits and behavioural abnormalities are clinical features of Duchenne muscular dystrophy. In order to better understand the mechanisms that underlie impaired brain functions in Duche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 98 publications
2
43
0
Order By: Relevance
“…It has been demonstrated that the dystrophin‐deficient mdx mouse displays alterations in learning, behavior, fear response, and memory . Glial fibrillary acidic protein was upregulated in the mdx‐4cv brain in an unbiased proteomic investigation, which is of considerable interest as it is a well‐established indicator of brain damage further evidencing brain involvement in DMD .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been demonstrated that the dystrophin‐deficient mdx mouse displays alterations in learning, behavior, fear response, and memory . Glial fibrillary acidic protein was upregulated in the mdx‐4cv brain in an unbiased proteomic investigation, which is of considerable interest as it is a well‐established indicator of brain damage further evidencing brain involvement in DMD .…”
Section: Resultsmentioning
confidence: 97%
“…A label‐free proteomic study comparing mdx‐4cv and wild‐type brains was conducted by Murphy et al. . Overall 1.78% of 2572 proteins detected in the mdx‐4cv brain were differentially expressed when compared to wild‐type.…”
Section: Resultsmentioning
confidence: 99%
“…Although dystrophinopathies are primarily classified as muscle diseases with characteristic neuromuscular symptoms [5], Duchenne muscular dystrophy is a multi-system disorder with severe complications due to cardiac failure, respiratory dysfunction, scoliosis, impaired liver metabolism, renal abnormalities and cognitive impairments [9]. Most studies into proteome-wide changes in non-skeletal muscle tissues [79][80][81][82][83][84][85][86] have focused on preparations from the dystrophin-deficient heart [38,[79][80][81]84], but muscular dystrophy-related effects on the brain [82,86], kidney [83] and liver [85] have also been studied by proteomics. Investigations using both gel-based and gel-free systems have established changed concentration levels in protein markers of energy metabolism, ion homeostasis, the extracellular matrix and cytoskeletal networks.…”
Section: Proteomic Analysis Of Non-skeletal Muscle Tissuesmentioning
confidence: 99%
“…Investigations using both gel-based and gel-free systems have established changed concentration levels in protein markers of energy metabolism, ion homeostasis, the extracellular matrix and cytoskeletal networks. Table 3 lists proteomic biomarker candidates from non-skeletal muscle tissues that are significantly changed in X-linked muscular dystrophy [79][80][81][82][83][84][85][86]. This includes cardiac-specific changes in the core dystrophin complex, mitochondrial enzymes, the basal lamina and associated extracellular matrix [38,[79][80][81]84], which might be linked to the cardio-respiratory syndrome in X-linked muscular dystrophy [5].…”
Section: Proteomic Analysis Of Non-skeletal Muscle Tissuesmentioning
confidence: 99%
See 1 more Smart Citation